2018
DOI: 10.1007/s10681-018-2146-y
|View full text |Cite
|
Sign up to set email alerts
|

The Eberhart and Russel’s Bayesian method used as an instrument to select maize hybrids

Abstract: Adaptability and stability analysis methods that use a priori information allow identifying and selecting potentially productive genotypes with greater accuracy. The aim of the current study is to use the Eberhart and Russel' Bayesian method as an instrument to analyze the adaptability and stability of hybrid maize cultivars and to assess the efficiency of using the distribution of informative and non-informative priors to select cultivars. Twenty-five (25) hybrid maize cultivars were assessed in 11 environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…The line BRS Esplendor showed that the estimate of stability parameter presented in the analysis using little informative priors (M3) disagreed with to those found in the analysis considering model M2. Similar results were also found by Nascimento et al (2011), Couto et al (2015) and Oliveira et al (2018).…”
Section: Discussionsupporting
confidence: 91%
“…The line BRS Esplendor showed that the estimate of stability parameter presented in the analysis using little informative priors (M3) disagreed with to those found in the analysis considering model M2. Similar results were also found by Nascimento et al (2011), Couto et al (2015) and Oliveira et al (2018).…”
Section: Discussionsupporting
confidence: 91%
“…Oliveira et al [30] evaluated 25 hybrid maize in 22 environments, divided between the states of Maranhão, Piauí and Sergipe, and observed two genotypes with specific adaptability to favorable environments and only four, of the 25 genotypes, with specific adaptability to unfavorable environments. The other genotypes were considered general adaptability.…”
Section: Discussionmentioning
confidence: 99%
“…Complex interactions between genotype and environment can occur, where certain combinations of genotype and environment may have synergistic or antagonistic effects that amplify or reduce plant performance. Therefore, considering and understanding the G × E interaction is crucial for the development of more effective genetic improvement strategies and the selection of varieties adapted to different environmental conditions [30].…”
Section: Discussionmentioning
confidence: 99%